The Effect of Adding Carrot Flour (Dacus Corota L) on the Water Content and Sensory Quality of Dry Pour Cakes - Bunga Switaloca; Mahdiyah; Ridawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to determine and analyze the effect of adding carrot flour on the moisture content and sensory quality of dried milk. The study was conducted at the Pastry and Bakery Processing Laboratory of the Culinary Arts Education Program at Jakarta State University. The study period ran from May 2025 to June 2026. The method used in this study was the experimental method. The research samples consisted of dried sus with 2%, 4%, and 6% added carrot flour, which were then tested by 45 moderately trained panelists—15 panelists each—who evaluated the dried sus products with added carrot flour (2%, 4%, and 6%) in terms of their sensory quality. Based on the results of the statistical hypothesis test for moisture content using an ANOVA test, it was shown that, overall, there was no effect of adding 2% (2.03), 4% (2.04), and 6% (2.05) carrot flour to the dried milk on moisture content. Based on the results of the statistical hypothesis test for sensory quality using the Kruskal-Wallis test, it was shown that the addition of 2%, 4%, and 6% carrot flour to the dried milk had no effect on the aspects of carrot flour aroma, savory taste, carrot flour taste, and texture. Based on the results of the Kruskal-Wallis test, it was shown that only the color aspect differed significantly, with the addition of 2% carrot flour yielding the best results. Thus, the author recommends that dried milk with 2% carrot flour be further.